Magnetoresponsive Discoidal Photonic Crystals Toward Active Color Pigments. (28th May 2014) - Lee, Hye Soo; Kim, Ju Hyeon; Lee, Joon‐Seok; Sim, Jae Young; Seo, Jung Yoon; Oh, You‐Kwan; Yang, Seung‐Man; Kim, Shin‐Hyun
<x xml:space="preserve">Abstract</x> Photonic microdisks with a multilayered structure are designed from photocurable suspensions by step‐by‐step photolithography. In each step of photolithography, either a colloidal photonic crystal or a magnetic‐particle‐laden layer is stacked over the windows of a photomask. Sequential photolithography enables the creation of multilayered photonic microdisks that have brilliant structural colors that can be switched by an external magnetic field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>